Penguatan Kapasitas Peternakan Menengah Melalui Teknologi Mesin Pengaduk Pakan Ternak Oleh Mahasiswa Teknik Mesin Universitas Simalungun - Sitopu, Joni Wilson; Saragih, Darwan Edyanto; Fauzi, Ahmad; Alfarizi, Rofi (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
Medium-scale goat farmers in Pematangsiantar still mix feed manually, resulting in inhomogeneous mixing and long work times. This Community Service project aims to empower farmers through the implementation of a livestock feed mixer machine based on appropriate technology. The method used is a participatory community service approach with primary data from observations, interviews, and machine performance tests, as well as secondary data from technical literature. The results show an increase in mixing time efficiency from approximately 20 minutes to approximately 10 minutes per batch, with a homogeneity level above 90%. The machine is easy to operate and energy efficient. In conclusion, the machine designed by Mechanical Engineering students at Simalungun University effectively increases production capacity, work efficiency, and the independence of medium-scale farmers.